The relationship between age-related development of spike-and-wave discharges and the resistance to amygdaloid kindling in rats with genetic absence epilepsy - ONAT, FİLİZ; GÜLHAN, REZZAN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2008)
Genetic Absence Epilepsy Rats from Strasbourg (GAERS) are resistant to amygdaloid kindling. Since in GAERS the characteristics of spike-and-wave discharges (SWDs) change with age, we have studied the relation between SWD maturation and the development of kindling resistance. Non-epileptic Wistar rats and GAERS were stimulated in basolateral amygdala with 400 mu A at 20 min intervals until they reached stage 5 seizures or for a maximum of 36 stimulations. All of the Wistar rats, the postnatal (PN) day 20 GAERS and the (kindling-prone) subgroups of GAERS at PN30 and PN60 reached stage 5 seizures; at PN20, PN30 and PN60 kindling rates were significantly slower in GAERS compared to Wistar rats. At PN30 and PN60, 41% and 69% of GAERS, respectively, showed no stage 3, 4 or 5 seizures after 36 stimulations (kindling-resistant subgroups). The SWD maturation involves changes in spectral patterns and correlate with age-related increases in kindling resistance in GAERS. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Temporal lobe epilepsy model; Absence epilepsy model; GAERS; Amygdaloid stimulation; Limbic seizures; Kindling resistance; ELECTRICAL-STIMULATION; SEIZURES; MECHANISMS; MODEL; EXPRESSION; NEURONS